Description of Fumariphilus Nieves-Aldrey, gen. nov., a new genus of herb gall wasps, with a key to genera of the tribe Aulacideini (Hymenoptera: Cynipidae) - Nieves-Aldrey, José Luis (Zootaxa, 2022)
A new genus of herb gall wasps, Fumariphilus Nieves-Aldrey gen. nov., (Hymenoptera, Cynipidae, Aulacideini), is described. Previous molecular phylogenetic analyses, and resulting systematic changes at the tribe level, have shown that the related species Aylax hypecoi Trotter and Neaylax versicolor Nieves-Aldrey have been incorrectly placed within their respective genera. In order to reflect their monophyletic lineage and to accommodate these species within the tribe Aulacideini, it is necessary to erect a new genus. The two species, Fumariphilus versicolor (Nieves-Aldrey, 1985) n. comb. and Fumariphilus hypecoi (Trotter, 1913) n. comb. placed in the new genus induce galls in fruits of species of, respectively, Hypecoum L. (Papaveraceae: Fumarioideae: Hypecoeae) and Fumaria L. (Papaveraceae: Fumarioideae: Fumarieae), reflecting a host-plant association that is unique among all the cynipids. Diagnostic morphological features of both the adult and the larvae and an identification key to the species of the new genus are provided. Adults of Fumariphilus versicolor n. comb., are also re-described and, for both species of Fumariphilus, the terminal instar larva is described and illustrated with SEM images. Following the erection of the new genus Fumariphilus, Aylax Hartig, sensu Nieves-Aldrey, 1994 is now sufficiently delimited within the tribe Aylacini sensu stricto Ashmead, 1903, which comprises species associated with only plants of the genus Papaver (Papaveraceae). Likewise, Neaylax Nieves-Aldrey, 1994, which now includes only the gall wasp species that associate with species of Salvia (Lamiaceae), is sufficiently delimited within the tribe Aulacideini Nieves-Aldrey, Nylander & Ronquist, 2015. Also provided in this work is an updated and illustrated identification key to the genera of the Aulacideini.